Influence of the wetting angle on capillary forces in pressure infiltration. (1st June 2015) - Léger, Alain; Weber, Ludger; Mortensen, Andreas
Abstract: This work probes the influence of wetting on pressure infiltration. Pressure/saturation curves for the infiltration of packed F1000 angular alumina particle preforms by liquid Cu–Al and Sn–Al alloys are measured using an instrumented high-temperature pressure infiltration apparatus. These are ceramic–metal systems in which the contact angle is documented to vary significantly with alloying, from non-wetting to wetting conditions. We show that adding Al to Sn or to Cu modifies the early percolation-dominated phases of infiltration and also the later, pore geometry dominated, phase of the infiltration process. Changes in contact angle brought by alloying cause the saturation/pressure curves to shift, yet for all systems of this work the curves remain entirely in the range of positive pressures, despite a transition to contact angles below 90°. Combining measured pressures for infiltration at fixed saturation with relevant sessile drop experiment data from the literature shows that for, the range of conditions explored here, the infiltration pressures required are proportional, not to the work of immersion, but to a linear function thereof. This result agrees qualitatively with prior work in the literature on the infiltration of non-metallic liquids in porous media, and provides a master curve by means of which saturation curves and sessile drop data can be reconciled for this particular packed ceramic particle preform.